Max and Marla - Boiger, Alexandra (G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2015)
"Max and Marla are best friends. And aspiring Olympians! With their eyes on the prize, they know exactly what it'll take to reach sledding success: preparation, practice and perseverance"--